2008
DOI: 10.1001/archophthalmol.2007.76
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure–Lowering Effects and Safety of Topical Administration of a Selective ROCK Inhibitor, SNJ-1656, in Healthy Volunteers

Abstract: To investigate the effects and safety of topical administration of an ophthalmic solution of a selective Rho-associated coiled coil-forming protein kinase (ROCK) inhibitor, SNJ-1656, 0.003% to 0.1%, in healthy male adult volunteers.Design: Randomized, double-masked, group-comparison, phase 1 clinical study. In the initial singleinstillation trial, 45 healthy volunteers were randomly subdivided into 5 groups and treated with SNJ-1656 in concentrations of 0.003%, 0.01%, 0.03%, 0.05%, and 0.1% in stepwise fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 20 publications
3
104
0
1
Order By: Relevance
“…The adverse event of ocular hyperemia has been reported previously in several clinical trials with Rho kinase inhibitors. 21,22 It was suggested that the hyperemia could be the result of blood vessel relaxation, as ROCK inhibition induces smooth muscle relaxation. 22 Hyperemia was not noted in the preclinical pharmacology monkey studies, perhaps because it is hard to see the vessels through the heavily-pigmented anterior conjunctiva and hard to see the more posterior but less pigmented conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse event of ocular hyperemia has been reported previously in several clinical trials with Rho kinase inhibitors. 21,22 It was suggested that the hyperemia could be the result of blood vessel relaxation, as ROCK inhibition induces smooth muscle relaxation. 22 Hyperemia was not noted in the preclinical pharmacology monkey studies, perhaps because it is hard to see the vessels through the heavily-pigmented anterior conjunctiva and hard to see the more posterior but less pigmented conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Interference with TM/IWSC cellular contractility, and cell-cell or cell-extracellular matrix adhesion, whether by inhibiting the Rho kinase or myosin light-chain kinase cascades or by disrupting actin microfilaments (whether by direct disruption or inhibition of their assembly) can result in increased outflow facility in live nonhuman primates 10,14,15 and in both human and primate organ-cultured anterior segments. [16][17][18][19][20] Several Rho kinase inhibitor compounds are in development [21][22][23][24][25][26] aiming to lower IOP by targeting trabecular outflow. Another novel agent targeting the TM is latrunculin B (Lat-B), which originates from Latrunculia (now Negombata) magnifica, a sponge from the Red Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, we and others have reported the role of RhoA signaling in the regulation of IOP (33,70). Treatment of perfused human eye cultures with adenoviruses carrying dominant negative RhoA results in lowering IOP (70) and inhibitors of Rho kinase (ROCK), which is activated by active RhoA, induces a reduction of IOP in rabbits (33) and has a lowering IOP effect in healthy volunteers (62). It is possible then to consider that a podoplanin increase in the trabecular meshwork with elevated IOP would likely lead to RhoA activation and thus have detrimental consequences for outflow facility.…”
Section: Discussionmentioning
confidence: 99%
“…The mean IOP reduction was -3.1 mmHg at 8 h after instillation in the 0.4% group, and all groups presented mild conjunctival hyperemia. The ROCK inhibitor SNJ-1656 was also demonstrated to be a safe hypotensive topical agent in human eyes (50) . All recent human clinical trials have showed that mild-to-moderate conjunctival hyperemia is the main adverse effect of ROCK inhibitors (47)(48)(49)(50)(51)(52) .…”
Section: Undesirable Effects Of Rockmentioning
confidence: 99%